REFLECTIVE PRACTICE AND SELF-IDENTITY AS PARTS OF PROFESSIONAL DEVELOPMENT: A SURVEY IN A TERTIARY LEVEL - Lulu Laela Amalia (E-LINK JOURNAL, 2019)
This study aims at revealing the knowledge of the teachers on the concept of reflective practice and self-identity as parts of professional development in an EFL higher education context. Reflective practice is closely related to the idea of learning from experience (Thomson & Pascal, 2012) and ithas been an important activity since 1980s in western education. Unfortunately, it has not been treated as one in Asian context, let alone in Indonesia. Despite the debate on the constant definition of reflective practice, investigating the understanding of the concept is yet thought-provoking. Thus, this study involves some teachers in tertiary level from both state and private universities in Indonesia. The data in this study are gained through distributing a Likert scale questionnaire on the knowledge of Reflective Practice and self-identity and an interview as a follow up data collection method in order to have thorough information. The result of the study shows that almost all teachers are aware of both concepts and their benefits for their professional development. Key words: Reflective practice, Professional development, Self-identity